Conformational Dynamics of Insulin - Hua, Qing-xin; Jai, Wenhua; Weiss, Michael A. (Frontiers in Endocrinology, 2011)
We have exploited a prandial insulin analogue (insulin lispro, the active component of Humalog®; Eli Lilly and Co.) to elucidate the underlying structure and dynamics of insulin as a monomer in solution. Whereas NMR-based modeling recapitulates structural relationships of insulin crystals (T-state protomers), dynamic anomalies are revealed by amide-proton exchange kinetics in D2O. Surprisingly, the majority of hydrogen bonds observed in crystal structures are only transiently maintained in solution, including key T-state-specific inter-chain contacts. Long-lived hydrogen bonds (as defined by global exchange kinetics) exist only at a subset of four -helical sites (two per chain) flanking an internal disulfide bridge (cystine A20-B19); these sites map within the proposed folding nucleus of proinsulin. The anomalous flexibility of insulin otherwise spans its active surface and may facilitate receptor binding. Because conformational fluctuations promote the degradation of pharmaceutical formulations, we envisage that “dynamic re-engineering” of insulin may enable design of ultra-stable formulations for humanitarian use in the developing world.